Perlindungan Hukum terhadap Anak sebagai Korban Tindak Kekerasan Seksual di Indonesia - Denta Rahma Suprapto; Enny Ristanti; Muhari Agus Santoso; Raditya Feda Rifandhana (Bhirawa Law Journal, 2021)
Children are the future generation, so that a good and bad nation is reflected in the behavior of children at this time. The current reality is that criminal acts against children are very frequent, especially criminal acts that cause children to experience profound psychological disorders and affect the child's development. This study examines how legal protection is provided to children as victims of sexual violence that is rife against children, and to find out what obstacles are faced in providing legal protection to child victims from acts of sexual violence. This study uses a sociological juridical approach, namely primary data collection or data collection through interviewing informants and secondary data collection or through literature study. The results of this study were that there were still many acts of sexual violence committed against children, most of these acts were committed by close people or from their own families. Children who are victims of sexual violence must receive special protection that can support the psychological recovery of the child. Apart from that, the lack of legal protection forchild victaims of sexual violence is the lack of awareness on the part of their parents or their immediate family to report these acts to the authorities.